Pengaruh Iklan Obat Bebas Non Resep di Televisi Terhadap Perilaku Swamedikasi pada Penggunaan Obat Pereda Gejala Flu di Jawa Barat - Hadi, Ezra Aurelia Glenia; Destiwati, Rita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Drug advertisements broadcast through television persuasively sell drug products by providing information about drugs and health so that the audience has interest and trust in choosing the drug product and then buying it to perform self-medication. Self-medication is a situation when a person uses medicines to treat diseases or symptoms that they recognize. The purpose of this study is to measure the effect of non-prescription over-the-counter drug advertisements aired on television with self-medication behavior on the use of non-prescription flu symptom relief drugs in West Java. The research method used is simple linear regression by testing normality, data determination test, and hypothesis testing. Significant results were obtained from testing the dependent and independent variables. The conclusion is that drug advertisements on television influence people in treating themselves, especially in handling flu symptoms. That way, advertising as a marketing communication medium for a drug company has succeeded in achieving the objectives and functions of the advertisement itself.